The Trade of Sago in Ambon, 1880-1900 - Putri Maya Masyitah; Endang Susilowati; Singgih Tri Sulistiyono (Diponegoro University, 2020)
During the late 19th century, sago in Ambon turned out not only to be a subsistence crop used as a staple food, but also as a commercial crop. Historical sources shown that sago became one of the important commodities in trade in the 19th century, as one of the commodities that affected the economy of the Ambonese people and the colonial government. Sago became a prominent commodity when the spices trade decreased. So, there is commercialization process of sago as an important trade commodity. In this connection, this article examines several issues, the sago became a strategic commodity and the role of sago in the Ambonese economy during 1880-1900. It is analyzed by using the historical method, which emphasized on primary sources based on official reports in the form of colonial publications. According to the study, between 1880 -1900 it was known that the local community and colonial government traded the sago. One interesting thing is that aside from being a staple food, sago is also used as a currency that is bartered with other commodities that have the same value. For the colonial government, sago became a commercial commodity that was quite productive, even having become an export commodity to various countries, such as Singapore and Europe. The colonial government sold sago in various forms such as bundles, basketry, slabs, flour, and grains. In addition, the government also rents sago lands to Christians and Muslims merchants for a specified period and cost.